The Role of Pricing in Increasing Customer Satisfaction: Analysis of The Barbershop Services Industry in Makassar City - Musa, Chalid Imran (PT. Maju Malaqbi Makkarana, 2023)
This research aims to analyze the role of price in increasing customer satisfaction in the barbershop service industry in Makassar City. The barbershop services industry has grown rapidly in recent years, and competition between service providers has become increasingly fierce. One factor that influences customer decisions is the price offered by the service provider. Therefore, this research aims to explore how price can influence customer satisfaction in the barbershop context. This research uses a quantitative approach by collecting data through questionnaires distributed to barbershop customers in Makassar City. Data processing was carried out using regression analysis to identify the relationship between price and customer satisfaction. The research results show that price has a significant influence on customer satisfaction in the barbershop service industry. These findings indicate that barbershop service providers need to consider appropriate pricing strategies to increase customer satisfaction. Competitive prices and in line with the quality of services offered can provide added value for customers. Apart from that, this research also shows that there are other factors that can influence customer satisfaction, such as service quality, barbershop environment, and overall customer experience. This research contributes to the understanding of the role of price in increasing customer satisfaction in the barbershop service industry. The results of this research can be a reference for barbershop service providers in developing effective marketing strategies to increase customer satisfaction and maintain competitiveness in a competitive market.